Using pepa to model the unemployment problem - Elrayes, amani; Nosseir, ann (Memo No ؛, 2010)
In this paper, we use performance evaluation process algebra pepa to model the interactivity between different variables affecting unemployment in four basic modules representing the balance between jop seekers and jop oppotunities.